Answer:
[tex](b)\ 2 * (7 + 8) = (2 * 7) + (2 * 8)[/tex]
Step-by-step explanation:
Given
[tex](a)\ 2 * (7 + 8) = (2 + 7) * (2 + 8)[/tex]
[tex](b)\ 2 * (7 + 8) = (2 * 7) + (2 * 8)[/tex]
[tex](c)\ 2 * (7 + 8) = (2 * 7) + 8[/tex]
Required
Which illustrates distributive property of multiplication over addition
The property states that:
[tex]a(b + c) = a * b + a * c[/tex]
By comparison
[tex]a = 2\ b = 7\ c = 8[/tex]
So, we have"
[tex]2(7 + 8) = 2 * 7 + 2 * 8[/tex]
[tex]2(7 + 8) = (2 * 7) + (2 * 8)[/tex]